FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI MASYARAKAT DI POSYANDU KELURAHAN LAHENDONG - Rivolta G.M. Walalangi; Henry S. Imbar; Greyti Wuisang (Jurnal GIZIDO, 2014)
Infants under five years old (Toddlers) is one of the goals posyandu quite important, becausea toddler is a sizeable proportion of the composition of the population of Indonesia, so theanalysis of the factors that encourage mothers to visit keposyandu needs to be done (MOH,RI 2007) .Ibu which do not weigh their babies to Posyandu terpantaunya can cause growthand development of infants. Toddlers are not weighed consecutive nutritional risk situationdeteriorated so impaired growth (MOH, 2006). The purpose of this study to determine thefactors associated with the level of participation of the community to visit keposyandu, in thevillage Lahendong South Tomohon sub districtThis research is a survey research with descriptive approach. Number of samples 45 people,the study was conducted in South Tomohon sub district KelurahanLahendong for 1 week.Respondents in this study were mothers with young children and mothers who are willing tobecome respondents, data collection in this study by using a questionnaire. The resultsshowed the majority of toddlers rarely below to Posyandu, that there are as many (75.6%)infants were not under posyandu faithful bbulan. Factors influencing that there is one factorage, maternal age, maternal education, and the role of cadres Posyandu distance. Based onthe research results also in the know that of all five factors that most influence on people'sparticipation, namely age, maternal age, and distance posyandu.